Pengaruh Pemberian Aspirin terhadap Gambaran Histopatologi Mukosa Gaster Mencit - Moammar Rizky Farhan; Oktora, Meta Zulyati; Dita Hasni (As-Shiha: Jurnal Kesehatan, 2022)
Aspirin is a group of non-steroidal anti-inflammatory drugs (NSAIDs) that are widely used by the public to treat rheumatic diseases. Apart from its anti-inflammatory role, aspirin is also an anti-thrombotic agent used in coronary heart disease (CHD) to prevent platelet aggregation. Aspirin is also a potent anipyretic. To determine the gastric mucosal histopathology of mice after being induced by apirin. The scope of the research is Medical Pathology, Anatomy and Pharmacology. The research was conducted at the Pharmacology Laboratory of the Faculty of Pharmacy, Andalas University and for reading the results at the Anatomical Pathology Laboratory, Faculty of Medicine, Baiturrahmah University. This research was conducted in March 2020 - January 2021. This research is a laboratory experimental. The samples used in this study were mice (Mus Musculus) aged 4-6 weeks with a body weight ranging from 18-20 grams. A sample of 18 mice was divided into 2 treatment groups, namely, positive and negative control samples. Aspirin was administered orally using a sonde for 3 consecutive weeks in positive control samples, and negative control samples were not treated. On the 27th day the termination was performed, the stomach was taken and histopathological preparations were made. The results of this study of 9 samples found 22.2% (2 samples) experienced desquamation, 44.4% (4 samples) experienced erosion, 33.3% (3 samples) experienced ulceration. Desquamation characteristics can be seen from the peeling of the uppermost layer of the gastric mucosa. And erosion can be seen from the loss of some areas of the gastric mucosa. Then for ulceration where the entire thickness of the mucosa is lost. There was a change in the picture in the gastric mucosa histopathology of mice (Mus musculus) after being induced by aspirin.